Meningite tuberculosa no Hospital Universitário João de Barros Barreto no período de 1999 a 2006. - ONUMA, Clara Santana da Rocha Lima (2022)
The central nervous system by Mycobacterium tuberculosis is a major challenge to public health ahead of the increasing impoverishment of our population and high prevalence of tuberculosis in our country. Allied to this we have the spread of Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome produces contours that the convergence of two important diseases. The University Hospital João de Barros Barreto is the institution of reference for infectious and parasitic diseases in Pará, which remains within the northern region, as the state with the highest number of hospitalizations and cases of tuberculous meningitis. The disease caused by Mycobacterium tuberculosis in the central nervous system affects not only the meninges but also the brain parenchyma and the vessels of the brain. This dissertation aims to describe the general clinical and epidemiological profile of menigoencefalite in hospitalized patients in the hospital during the period from January 1999 to December 2006. We analyzed the charts of all patients with reported cases of meningoencephalitis by Mycobacterium Tuberculosis by the Center for Epidemiological Surveillance totaling 106 patients of which 77 corresponded to patients with tuberculous meningitis and 29 patients co-infected HIV-TB meningitis. There was predominance of the age group between 20 to 39 years and in children under 3 years only in patients with tuberculous meningitis, while in co-infected patients, the predominant age range was between 30 to 39 years. Most patients were unmarried as marital status, in both groups. It was evidenced a predominance of patients from the interior of the state, the only group affected by tuberculous meningoencephalitis. While in co-infected the majority of the capital was founded.. In the analysis of cerebrospinal fluid obtained is that only patients with tuberculous meningitis, have an approximately 4 times greater chance of having the type mononuclear cells for patients co-infected. The diagnosis was clinical in most cases in both groups. With respect to the proposed treatment, we observed that the scheme II associated with corticosteroids was introduced to most patients, regardless of the group. The research envidenciou the high rate of mortality caused by the MT as well as the influence of such co-infection on clinical outcome of these patients.